1987
DOI: 10.1017/s002211208700051x
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of the steady and unsteady flow characteristics of stirred reactors

Abstract: Liquid flow in a baffled stirred reactor vessel driven by a six-blade disk impeller has been investigated experimentally. Laser-slit photography provided an overview of the flows which were quantified by measurements of velocity characteristics, obtained with a laser-Doppler anemometer, for an impeller rotational speed of 300 r.p.m. and for three impeller clearances from the bottom of the vessel. The mean flow results show an inclination of the impeller stream and the formation of ring vortices above and below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
149
2
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(171 citation statements)
references
References 8 publications
18
149
2
2
Order By: Relevance
“…11. It may be observed that MI intensity is significantly higher in the discharge stream The above description of MI may be in contrast with the type of MI phenomena reported in literature for RDT and PBT impellers (Yianneskis et al, 1987;Haam et al, 1992;Guillard et al, 2000;Nikiforaki et al, 2003). A common factor amongst the aforementioned studies is that MIs persist close to the liquid surface, circulate around the shaft or form behind the baffles, whereas in the present case, the MIs have a relatively larger probability of occurrence in the discharge stream.…”
Section: Macro-instabilitiescontrasting
confidence: 76%
See 1 more Smart Citation
“…11. It may be observed that MI intensity is significantly higher in the discharge stream The above description of MI may be in contrast with the type of MI phenomena reported in literature for RDT and PBT impellers (Yianneskis et al, 1987;Haam et al, 1992;Guillard et al, 2000;Nikiforaki et al, 2003). A common factor amongst the aforementioned studies is that MIs persist close to the liquid surface, circulate around the shaft or form behind the baffles, whereas in the present case, the MIs have a relatively larger probability of occurrence in the discharge stream.…”
Section: Macro-instabilitiescontrasting
confidence: 76%
“…This type of behaviour does not conform to the traditional view of MI, which endure for longer periods (e.g. 10 s identified by Yianneskis et al (1987) for an RDT). The only firm conclusion that can be drawn thus far is that low-frequency phenomena (between 0-200 Hz, and hence lower relative to the tooth passage frequency of 900 Hz) have been detected for the EkatoMizer.…”
Section: Macro-instabilitiescontrasting
confidence: 56%
“…These flows are transient, since trailing vortices are formed in the wake of the blades, so that the flow varies periodically close to the impeller (Yianneskis et al, 1987). In addition, stirred tanks containing wall baffles or fixed internals, such as heating coils or dips pipes are challenging to simulate using CFD, because the shape of the flow domain is not fixed in time.…”
Section: Representation Of the Impellermentioning
confidence: 99%
“…For such a configuration of the apparatus, knowledge related to the liquid flow within the vessel has been accumulated for utilization in operational and geometrical design . Dynamics of the bulk flow produced by the turbine-type impeller within the vessel were documented by a number of researchers (Yianneskis et al, 1987;Mavros, 2001). Additionally, the characteristics of the liquid flow were elucidated for the region in the vicinity of the impeller, which is essential in the apparatus Yoon et al, 2001).…”
Section: Introductionmentioning
confidence: 99%